Physiological and Transcriptome Analysis Reveal the Underlying Mechanism of Salicylic Acid-Alleviated Drought Stress in Kenaf (Hibiscus cannabinus L.) - Hui Zhang; Guofeng Xu; Samavia Mubeen; Rujian Wei; Muzammal Rehman; Shan Cao; Caijin Wang; Jiao Yue; Jiao Pan; Gang Jin; Ru Li; Tao Chen; et al. (Life)
Salicylic acid (SA) plays a crucial role in alleviating drought stress in plants. However, little is known about the molecular mechanisms underlying exogenous SA on the drought tolerance of kenaf. In this study, the kenaf seedlings were subjected to physiological and transcriptomic analysis under control (CK), moderate drought stress (D), and moderate drought stress with 1 mM SA (D_SA). Under drought conditions, SA significantly improved the plant biomass, leaf area, antioxidant enzyme activities (SOD, POD, and CAT), soluble sugars, starch and proline contents, and photosynthesis, while the contents of MDA, H2O2, and O2− were significantly decreased. A total of 3430 (1118 up-regulated and 2312 down-regulated) genes were differentially expressed in group D, compared with group CK. At the same time, 92 (56 up-regulated and 36 down-regulated) genes were differentially expressed in group D_SA compared with group D. GO and KEGG analysis showed that the differentially expressed genes (DEGs) were enriched in various metabolic pathways, such as carbohydrate metabolism, lipid metabolism, and the metabolism of terpenoids and polyketides. Results showed that the genes related to the antioxidant system, sucrose and starch synthesis, osmoregulation, ABA signal regulation, and differentially expressed transcription factors, such as AP2/ERF4 and NF-Y1, were involved in the increased drought tolerance of kenaf under exogenous SA. Virus-induced gene silencing (VIGS)-mediated silencing of salicylate binding protein 2 gene (HcSABP2) decreased the drought resistance of kenaf seedlings. Thus, the present study provides valuable insights into the regulatory mechanism of exogenous SA in alleviating drought stress in kenaf.